Dinamika Historis dan Jaringan Intelektual Pondok Pesantren di Provinsi Kepulauan Bangka Belitung Tahun 1930-2020 - Hasan Asari; Abd. Mukti; Subri Subri (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
The focus of this article is to find out the historical dynamics and intellectual network of pesantren in Bangka. The research method is the historical method of Kuntowijoyo's theory. The result of the research is that the dynamics of the history of Islamic boarding schools in the province of the Bangka Belitung archipelago began with traditional Islamic educational institutions, namely reciting the Koran, then Arabic schools and then developing into Islamic boarding schools. The historical range of the growth of the Islamic boarding school is in accordance with the path of Islamization and the traditional characteristics of Bangka Islam. Meanwhile, the intellectual network of the pesantren of the Bangka community started from the Mecca and Middle East networks around the 1910s. Then the network shifted to its own country, which spread to parts of Sumatra, East Java, West Java and Kalimantan as well as the island of Bangka itself in the decade of the New Order era until post-reformation around the 1970s until now.